Pengaruh Tingkat Sensitivitas Gender Terhadap Sikap Mahasiswa Dalam Kasus Pelecehan Seksual Di UIN Syarif Hidayatullah Jakarta - Alda Okti Ramadini; Nabillah Afa Fillah; Riska Dewi Andriyani; Nasya Kamila Nayla Rasyid; Salman Al Farizi; Rini Laili Prihatini (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The increasing number of harassment cases occurring in society has raised concerns among various groups, including academic circles and prospective Islamic religious counselors. As agents of social change, students of Islamic Guidance and Counseling are expected to play a role and provide education in shaping public opinion and intervening in social issues. This study aims to examine the influence of gender sensitivity levels on the attitudes of Islamic Guidance and Counseling students in responding to cases of sexual harassment. The research was conducted using a quantitative approach with purposive sampling technique involving 75 relevant respondents who were in the process of value formation and had received basic gender-related material. The instrument used was a Likert scale, and the data were analyzed using simple linear regression with SPSS for Windows version 26. The results showed a positive and significant influence between gender sensitivity and students' attitudes toward sexual harassment cases, with a Pearson correlation coefficient of 0.708 and a significance value of 0.000 (p < 0.05). The R square value of 0.502 indicates that gender sensitivity explains 50.2% of the variation in students’ attitudes toward sexual harassment cases. These findings are supported by theories from John Money, Sandra Bem, Carol Gilligan, Albert Bandura, Lawrence Kohlberg, and Paulo Freire, which emphasize the importance of social experiences, moral values, and critical education in shaping gender awareness and attitudes toward gender injustice.